(untitled) - Konstam, Angus (Hoboken, N.J., 2006)
Drawing on vivid descriptions of Blackbeard's attacks from his rare surviving victims, pirate expert Angus Konstam traces Blackbeard's career from its beginnings to his final defeat in a tremendous sea battle near his base at Ocracoke Island. Presenting dramatic accounts of the pirate's very effective tactics and his reputation for cruelty, Konstam offers a fascinating examination of the life and business of piracy and the lure of this brutal and bloody trade.
Keywords: Pirates,Pirates; Atlantic Coast,North Carolina,Virginia,Atlantic Coast